Bioinspired Ferroelectric Polymer Arrays as Photodetectors with Signal Transmissible to Neuron Cells. Issue 48 (12th October 2016) - Chen, Xin; Pan, Shi; Feng, Pei‐Jian; Bian, Huafeng; Han, Xu; Liu, Jia‐Hao; Guo, Xu; Chen, Dongzhong; Ge, Haixiong; Shen, Qun‐Dong
Abstract : A bioinspired photodetector with signal transmissible to neuron cells is fabricated. Photoisomerization of the dye molecules embedded in the ferroelectric polymer membrane achieves electric polarization change under visible light. The photodetector realizes high sensitivity, color recognition, transient response, and 3D visual detection with resolution of 25 000 PPI, and, impressively, directly transduces the signal to neuron cells.